2022
DOI: 10.1111/emre.12492
|View full text |Cite
|
Sign up to set email alerts
|

Towards a general framework for innovation shaped with AI to create and transform market offerings

Abstract: Our research focuses on early‐stages of innovation, especially in the Biotech and Pharmaceutical industry, wherein the business research is still hit‐and‐miss, mainly based on trial and error and experimentation. We leverage the story of a high‐growth startup, building and expanding on behavioral economics that examines the relationships between science and innovation, especially dynamic capabilities and related problemistic search and strategic options generation. A general framework for innovation shaped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
1
0
1
Order By: Relevance
“…Third, as digital affordances refer to action potentials that digital technologies represent for users with certain characteristics and purposes, it is important to consider the interactions between individuals and organizations and the digital technologies they use (Majchrzak & Markus, 2013). Besides delving more deeply into the role of specific digital technologies such as, for example, narrow and general artificial intelligence (Giacomoni, 2022), future research could examine which personality traits and organizational characteristics influence the perception of digital affordances of various digital technologies and how the mediating mechanisms theorized in this study are affected by them. In this context, future research might investigate the conditions under which the different mechanisms that we identified become relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Third, as digital affordances refer to action potentials that digital technologies represent for users with certain characteristics and purposes, it is important to consider the interactions between individuals and organizations and the digital technologies they use (Majchrzak & Markus, 2013). Besides delving more deeply into the role of specific digital technologies such as, for example, narrow and general artificial intelligence (Giacomoni, 2022), future research could examine which personality traits and organizational characteristics influence the perception of digital affordances of various digital technologies and how the mediating mechanisms theorized in this study are affected by them. In this context, future research might investigate the conditions under which the different mechanisms that we identified become relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Même l'ingénierie des systèmes, définie comme "a transdisciplinary and integrative approach to enable the successful realization, use, and retirement of engineered systems, using systems principles and concepts, and scientific, technological, and management methods" (Incose, 2022) 20 est impuissante, notamment en ce qui concerne les "levels of complexity, change, uncertainty and variety". Il en va de même de l'A.I., en incluant les Machine Learning, Deep (Reinforcement) Learning, etc., car l'univers des possibles ne peut pas être connu à l'avance (Giacomoni, 2022).…”
Section: Limites Operationnelles Et Theoriques Des Formalismes En Usa...unclassified